Genetic basis for natural variation in flowering time in local populations of Arabidopsis thaliana - McCulloch, Hayley Louise (The University of Edinburgh, 2012)
Factors affecting flowering time have been extensively studied for decades. Greater understanding of flowering time has wider implications in agriculture and ecology as the trait is crucial to optimising reproductive success. It is best understood in the genetic model Arabidopsis thaliana (Arabidopsis), in which loss and gain of function mutations have identified several pathways that regulate flowering and its response to the environment. This has been complemented by studies of natural variation in flowering. Worldwide accessions of Arabidopsis have been used to identify additional flowering regulators and to examine the evolution of these genes and their potential involvement in adaptation to different environments. One of the most extensively studied pathways is responsible for accelerated flowering in response to an extended period of cold (vernalization). Several studies have attributed a substantial proportion of worldwide variation to the genes FRIGIDA (FRI) and FLOWERING LOCUS C (FLC), both of which are instrumental in conferring sensitivity to vernalization, though other genes have also been found. This study examines flowering time variation locally in populations of Arabidopsis from in and around Edinburgh. It identifies substantial, genetically determined variation in flowering time and in sensitivity to photoperiod and vernalization between local accessions. Variation in FRI and FLC sequences and in their levels of expression were detected in local accessions, but these were able to explain little of the phenotypic variation observed. Hybrids between local accessions showing extreme differences in flowering time or responses to photoperiod and vernalization were therefore used to map genes underlying their differences as quantitative trait loci (QTL). This analysis identified a locus in chromosome 5 that could account for differences in vernalization sensitivity. This region includes the VERNALIZATION INSENSITIVE 3 (VIN3) gene. Sequence differences between VIN3 alleles and their expression in response to vernalization supported the potential involvement of this gene in local flowering time variation.
Keywords: flowering time; Arabidopsis; natural variation; vernalization